Statistical Analysis of Aquifer Hydraulic Properties by a Continuous Pumping Tomography Test: Application to the Boise Hydrogeophysical Research Site. Issue 12 (12th December 2022) - Cheng, Kan Bun; Dagan, Gedeon; Barrash, Warren; Cardiff, Michael; Rabinovich, Avinoam
Abstract: Characterizing aquifer heterogeneity is paramount for accurate flow and transport modeling. In this work, we present a new approach for statistical analysis of hydraulic properties in continuous pumping tomography tests of a phreatic aquifer. The method entails determining equivalent hydraulic conductivity ( K eq ), specific storage ( S s, eq ), and specific yield ( S y, eq ) at many locations in the field and then calculating statistical moments of the equivalent properties, assuming they are random space variables. Equivalent properties are defined as the ones pertinent to a homogeneous aquifer for which the head time dependent signal fits the one observed in the pumping test. Calculation is carried out in a novel approach, by matching measured head data to two separate semianalytical solutions considering two time periods, early and late. We apply this approach to the Boise Hydrogeophysical Research Site and find that the equivalent property spatial averages decrease with horizontal distance from the pumping well and appear to stabilize at sufficiently large distances, in line with existing theory for K eq . The squared coefficient of variation shows similar behavior, with values indicating a weakly heterogeneous aquifer. Furthermore, estimated values for K eq, S s, eq, and S y, eq are in agreement with literature values for the site. Key Points: New approach for statistical analysis of equivalent hydraulic properties (conductivity, specific storage, and specific yield) is presented Method is applied to tomographic pumping test data from the Boise aquifer to find mean and variance of equivalent properties The mean is shown to decrease with distance from pumping well and appears to converge to the effective value at a distance